Associations of smoking and biohazard exposure with Alzheimer's disease brain and plasma biomarkers in early old age. (31st December 2021) - Franz, Carol E; Whitsell, Nathan; Qin, Yongmei Amy; Tu, Xin M; Kremen, William S
Abstract: Background: Cigarette smoking and environmental exposure to other biohazardous chemicals and substances are associated with increased risk of developing cancer, cardiovascular disease, and other diseases that contribute to shorter life expectancy. Their associations with Alzheimer's Disease (AD)‐related brain indicators of structural integrity and plasma biomarkers are less often examined. Method: At average age 68 (range 61‐73), 1118 male participants in the Vietnam Era Twin Study of Aging (VETSA) self‐reported on cigarette smoking habits which we used to calculate pack years. Participants also self‐reported on prolonged or severe exposure to herbicides/pesticides, metal dust, Agent Orange, or other biochemical hazards. Using MRI data collected at average age 68 from approximately 470 participants, we examined a published an AD‐Brain signature based on thickness in 7 AD‐related cortical regions and hippocampal volume. We created a novel an AD‐Mean Diffusivity (AD‐MD) signature based on those same regions (higher AD‐MD scores being worse). We also examined a predicted brain age difference score (PBAD), an indicator of global accelerated brain aging. Plasma abeta42, abeta42/40 ratio, and total tau (t‐tau) were assayed using the Quanterix Simoa system. Multivariable analyses controlled for age, ethnicity, education, and the random effect of family (i.e., twin pairs). Results: Smoking pack years at age 68 were negatively associated with AD‐Brain Signature (p<0.0001) and PBAD (p=0.0013). Pack years (p=0.0001) and Agent Orange (p=0.047) were positively associated with AD‐MD Signature. T‐tau was positively significantly associated with smoking (p=0.0039) and Agent Orange (p=0.004). Conclusions: Heavier lifetime smokers had brains more similar to brains of adults with AD, showed accelerated brain aging, and had higher levels of t‐tau in early old age. All of these are indicators of higher risk for AD. Exposure to Agent Orange, a toxic herbicide, was also related to poorer structural brain integrity and t‐tau. Smoking had the strongest relationship with overall brain health in late midlife compared with other types of environmental exposures, reinforcing its role in pathological aging and its importance as a public health priority. The results suggest that more attention should be paid to potentially toxic environmental exposures that may increase risk for AD and other health conditions.